THERMALLY-OPTICALLY-THERMALLY STIMULATED LUMINESCENCE - Akpan, Dianabasi; Ekpo, Sunday; Effiong, Christopher; Aka, Mfoniso (IJRDO-Journal of Applied Science, 2023)
A three-stage energy band model was studied. The model consists of electrons thermally stimulated from the ground state to the first excited state, after which they were optically stimulated into the second excited state and they were finally stimulated thermally into the conduction band. A set of simultaneous differential equations was generated from the models and three assumed conditions were applied to this model, which they were solved analytically and analytical expressions were obtained. The same set of simultaneous equations were solved numerically using ode 15s MATLAB solver. When considering first-order peaks, the kinetic parameters obtained were found to be in good agreement with the analytical expressions. But when considering non first-order peaks, the kinetic parameters obtained numerically were not in good agreement with the analytical expressions and explanations had been given. Second-order peaks could not be obtained despite careful selection of the kinetic parameters because the traps were quickly saturated and the quasi- equilibrium conditions assumed could no longer be satisfied. The stability of the excited TA-OSL signals produced by the model was also studied. The real stability of the excited TA-OSL signals produced by this model was found to be about 46 million years.